The Effects of Diosmin on Kidney Morphology and Functions in Renovascular Hypertensive Rats - Mowong, Chompilat; Poasakate, Anuson; Chano, Banyaphon; Iampanichakul, Metee; Chaihongsa, Nisita; Rachiwong, Nutnicha; Pakeechote, Poungrat; Phuthong, Sophida; Maneesai, Putcharawipa (Srinagarind Medical Journal, 2023)
Background and objective: Renovascular hypertension associated with vascular and kidney dysfunctions have been reported. The possible mechanism might be related to oxidative stress. Diosmin is a flavonoid that is abundant in the Rutaceae family. It exerts numerous biological activities such as anti-oxidation and antihypertension. However, the study of diosmin in renovascular hypertension is still unexplored. Thus, the purpose of this study was to investigate the effects of diosmin on kidney morphology and function in two-kidney, one-clip (2K-1C) hypertension. Method: Male Sprague-Dawley rats (150-160g) were used in this study. The left renal artery was clipped with a silver clip to induce hypertension. Three weeks after the operation, the rats were divided into five groups (n=5/each) including sham rats treated with vehicle (1.5 ml/kg/day); 2K-1C rats treated with vehicle (1.5 ml/kg/day); 2K-1C rats treated with diosmin (50 and 100 mg/kg/day); and 2K-1C rats treated with telmisartan (5 mg/kg/day) for four weeks by oral gavage. Systolic blood pressure (SP) was measured weekly using the tail-cuff method. At the end of the experiment, the urine sample and the kidney of all rats were collected for biochemical and morphological studies. Results: Treatment with diosmin (100 mg/kg/day) significantly reduced high blood pressure in 2K-1C hypertensive rats (p < 0.05). Increases in kidney tissue malondialdehyde (MDA) and superoxide productions in 2K-1C rats were ameliorated by diosmin (100 mg/kg/day) (p < 0.05). It also improved kidney function via the elevation of creatinine (Cr) and blood urine nitrogen (BUN) in urine compared with untreated 2K-1C group (p < 0.05). Moreover, improved kidney morphology via reduced glomerular cross-sectional area (CAS), glomerular tuft area, Bowman's space area, and glomerular volume in the non-clipped kidney (p < 0.05). In addition, treatment with telmisartan had a similar effect to diosmin (100 mg/kg/day). Conclusion: Diosmin exerts an antihypertensive effect in renovascular hypertensive rats. It also improved kidney morphology and functions in 2K-1C rats. This effect might be relevant to its antioxidative effect.